2016
DOI: 10.1093/cid/ciw586
|View full text |Cite
|
Sign up to set email alerts
|

The Cervicovaginal Microbiota in Women Notified forChlamydia trachomatisInfection: A Case-Control Study at the Sexually Transmitted Infection Outpatient Clinic in Amsterdam, The Netherlands

Abstract: Women who tested positive for Chlamydia trachomatis infection after having been contact-traced by a chlamydia-positive partner were more likely to have CVM dominated by L. iners or by diverse anaerobic bacteria, than by L. crispatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
74
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 36 publications
7
74
1
1
Order By: Relevance
“…L. iners was present in a higher number in C. trachomatis positive women than in healthy controls and this finding is in accordance with previous studies, showing that C. trachomatis positive women were more likely to have a microbiota dominated by L. iners (Ma et al, 2013; van der Veer et al, 2017). This may be explained by the ability of L. iners to survive in a wide range of pH and other metabolic stress-related conditions, adapting to an altered cervico-vaginal environment (Petrova et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…L. iners was present in a higher number in C. trachomatis positive women than in healthy controls and this finding is in accordance with previous studies, showing that C. trachomatis positive women were more likely to have a microbiota dominated by L. iners (Ma et al, 2013; van der Veer et al, 2017). This may be explained by the ability of L. iners to survive in a wide range of pH and other metabolic stress-related conditions, adapting to an altered cervico-vaginal environment (Petrova et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…A similar alteration in cervico-vaginal microbiota related to C. trachomatis infection was also found by Ma et al (2013) and van der Veer et al (2017). …”
Section: Discussionsupporting
confidence: 85%
“…Similar to our findings in CT-negative women, CST-I, CST-III and CST-IV were the most prevalent vaginal microbiota types found in this population, though our study showed a higher proportion of CST-I in non-infected women. This over-representation of CST-I in non-infected women could be explained with an increased protection to STIs by a community dominated by L. crispatus as previously hypothesised by van der Veer et al 8. In their study of a high-risk population for STIs in the Netherlands, proportions of CST-I, CST-III and CST-IV in CT-negative women were 39.0%, 26.8% and 34.2%, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…is controversial. Low Lactobacillus levels are one indicator for bacterial vaginosis (BV) and have been associated with increased prevalence, susceptibility and transmission of sexually transmitted infections, including HIV, Neisseria gonorrhoeae, Chlamydia trachomatis and Trichomonas vaginalis [1014]. However, many asymptomatic women have vaginal bacterial communities that are not dominated by Lactobacillus sp.…”
Section: Introductionmentioning
confidence: 99%